Development of multiscale multiphysics-based modelling and simulations with the application to precision machining of aerofoil structures. Issue 3 (7th October 2020) - Shao, Yizhi; Adetoro, Oluwamayokun Bamidele; Cheng, Kai
Abstract : Purpose: This study aims to optimize the manufacturing process to improve the manufacturing quality, costs and delivering time with the help of multiscale multiphysics modelling and simulation. Multiscale multiphysics-based modelling and simulations are receiving more and more interest by research community and the industry particularly in the context of increasing demands for manufacturing high precision complex products and understanding the intrinsic complexity in associated manufacturing processes. Design/methodology/approach: In this paper, some modelling and analysis techniques using multiscale multiphysics modelling are presented and discussed. Findings: Furthermore, the possibility of adopting the multiscale multiphysics modelling and simulation to develop the virtual machining system is evaluated, and further supported with an industrial case study on abrasive flow machining (AFM) of integrally bladed rotors using the techniques and system developed. Originality/value: With the development of multiscale multiphysics-based modelling and simulation, it will enable effective and efficient optimisation of manufacturing processes and further improvement of manufacturing quality, costs, delivery time and the overall competitiveness.